Epilepsy and Literary creativeness: Fyodor M. Dostoevsky - FARI, FRANC (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
Among the most salient biographical aspects affecting an artistic or literary genius, chronic diseases generally play a crucial role in the creation and content of literary production. This held true also for the great Russian novelist Fyodor Mikhailovitch Dostoevsky (1821-1881) who for most of his life suffered from epilepsy. Dostoevsky was greatly influenced by epilepsy. In almost all his novels there is a character affected by this pathology. To identify all possible factors associated with epilepsy, I read the following works by Dostoevky: Poor Folk, The Double, The white nights, Uncle’s Dream, The House of Dead, The Insulted and Injured, Notes from the Underground, The Gambler, Crime and Punishment, The Eternal Husband, The Idiot, The Devils, The Adolescent, The Brothers Karamazov. All factors in line with a condition of epilepsy were classified as follows: 1) onset of epilepsy, 2) auras (in its various manifestations), 3) cry, 4) automatisms, 5) description of seizures, 6) post-ictal symptoms, 7) triggering factors, 8) interictal features. For each of these points, an excerpt of the novel, a short summary or a reference will be provided. In my opinion, Dostoevsky’s epileptic symptomatology allows to hypothesize that the novelist had a focal epilepsy localized in the frontal lobe (with involvement of the anterior cingulate gyrus) with a tendency to secondary generalization. In describing epilepsy, Dostoevsky probably had two objectives in mind. The first goal was to re-state that people suffering from epilepsy were not monsters. Dostoevky’s second objective was even more ambitious: not only people with epilepsy are like others but they show greater qualities in terms of cognition, philosophical and religious aspects than normal people.